Answer:
The zeroes of this equation would be -1 and a double root at 1.
Explanation:
To find these, start factoring by splitting. In this, we first only look at the first two terms. Then we pull out the greatest common factor.
x^3 - x^2
x^2(x - 1)
Now we do the same with the next two numbers.
-x + 1
-1(x - 1)
Now we can use the things outside the parenthesis along with the common parenthesis as the factors.
(x^2 - 1)(x - 1)
And we can factor the first parenthesis by using the difference of two squares model.
(x + 1)(x - 1)(x - 1)
And finally, we can find the zeroes by setting each parenthesis equal to 0.
x + 1 = 0
x = -1
x - 1 = 0
x = 1
x - 1 = 0
x = 1